Digital strategies for the use of Canva in the teaching of Ecuador regions - Proaño Benalcazar , Eliana Fabiola; Moncada Rangel , José Alí (SATHIRI, 2025)
Canva is a digital tool that enables the creation of infographics, presentations, and other materials that help visualize geographic concepts in an attractive way. This article aims to propose digital didactic strategies on the Canva platform for teaching about the regions of Ecuador in the 5th year of Ecuadorian Basic General Education. The research has a mixed approach and a descriptive scope. A survey was applied to a non-probabilistic sample of 20 teachers from six educational institutions in the city of Ibarra to diagnose the use of the Canva tool. Based on this diagnosis, strategies were designed considering the findings and the subject contents. The results showed that 70% of the teachers use traditional classes as part of their pedagogical practice and expressed their willingness to use Canva in the teaching process, considering the benefits it offers for students’ learning. As a result of the research, five strategies based on Canva were designed to promote meaningful and experiential learning, problem-based learning, and collaborative learning. This proposal was validated by the teachers, who considered the use of technological tools in teaching to be very important. In conclusion, the use of the Canva tool provides educators with the ability to customize teaching in a creative and motivating way, especially in the Social Studies subject.